Dye removal from simulated wastewater by using empty fruit bunch as an adsorption agent - Lokman, Faradilla (2006)
The use of cheap and ecofriendly adsorbents have been studied to find an alternative substitution of activated carbon for the removal dyes from wastewater. Adsorbence from empty fruit bunches (EFB) were taken from palm oil industries were successfully remove dye from simulated wastewater. In this study, dye solution (methyl violet) were added into empty fruit bunches (EFB) which been treated with formaldehyde and sulphuric acid. This experiment’s results were compared with result from similar experiment with powder activated carbon (PAC) which commonly use in industries to varying dye concentration, adsorbent dosage and pH. The result showed that the amount of the adsorbent was increased, the percentage of dye removal increased accordingly. An initial pH of the solution in the range 2-10 was favorable for the methyl violet removal for the adsorbent. The adsorption efficiency of different adsorbents was in order PAC>EFB Ttreated with sulphuric acid>EFB treated with formaldehyde. Adsorbents are very efficient in decolorized dilute solution. The empty fruit bunches (EFB) is a resource which has huge potential to be used for power generator. Today, it have been tried to use wastewater treatment as adsorption agent.